Pengaruh Lingkungan Kerja, Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Aparatur Sipil Negara (ASN) Di Kabupaten Tana Toraja - Silvan Tande Bura; Nurdin Brasit; Sumardi Sumardi (Magister Management, Hasanuddin University, 2019)
This study aims to determine the effect of the work environment, work discipline and work motivation on the performance of the state civil apparatus (ASN) in Tana Toraja district. This study uses descriptive and verification methods. The population in this study was part of the state civil apparatus (ASN) in Tana Toraja Regency, which amounted to 150 people. The sampling method is a purposive sampling. The type of data used is quantitative data collected using a questionnaire. The data analysis technique used in this study is quantitative analysis. The results of this study indicate that the work environment, work discipline, and work motivation simultaneously have a direct, positive and significant effect on performance. The work environment has a direct, positive and significant effect on performance. Work discipline has a direct, positive and significant effect on performance. Work motivation has a direct, positive and significant effect on employee performance. The most dominant variable influencing the performance of the state civil service (ASN) in Tana Toraja Regency is work discipline.